The Korean Cinderella - Shirley Climo (U.S.A HarperCollins Publishers, 1996)
'Climo and Heller conflate several Korean variants of Cinderella to offer up the story of Pear Blossom, a lovely girl who is sorely mistreated by her nasty stepmother and stepsister.... At once comfortingly familiar and intriguingly exotic, the text is especially noteworthy for its instructive but unobtrusive incorporation of Korean words.'--Publishers Weekly. 'Heller's paintings are exotically lush and colorful as well as engaging.... An agreeable retelling of the Cinderella story.' --BL. Notable 1994 Children's Trade Books in Social Studies (NCSS/CBC)
Keywords: How We Express Ourselves -- -Beliefs and Values; Fairytale -- Read Aloud + Anthology-Folk Tales + Circle Time